The politics of horizontal inequality: Indigenous opposition to wind farm development in Mexico - Courtney Jung (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In less than a decade, foreign investors have erected more than 3,200 wind turbines across the Isthmus of Techuantepec investing billions of dollars and generating more than 90 per cent of Mexico's wind energy. The isthmus is also home to more than one thousand indigenous communities whose ancestors settled in the region roughly 3,000 years ago. In most cases, wind farm construction has proceeded without significant community opposition. More recently, however, some indigenous communities have begun to protest against the wind turbines that are taking over their land and transforming their landscape. An intersectional approach highlights two distinct features of the politics of horizontal inequality. First, political strategies and demands may shift over time and across issue areas - opposition to windmills may be generated by exclusion from decision-making, inadequate compensation, or the violation of sacred land. Second, the lens of intersectionality focuses attention on the ways that such categories as race, class, ethnicity, gender, language and region intersect to challenge the 'group-ness' of any one of these categories. In the case of indigenous opposition to wind technology in Mexico, intersectionality explains the particular challenges inherent in securing 'free prior and informed consent', a cornerstone of contemporary policy toward indigenous peoples.
Keywords: Q40; Y80; Z13; 330; ethnicity; horizontal inequality; indigenous peoples; intersectionality; Mexico